Integracja działalności innowacyjnej organizacji w sieci - Dolińska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Now clusters are developed where firms collaborate among themselves in network organization area, during innovation processes execution. Innovation process consists its of the following activities: search of innovation conception, solution elaboration, innovation application or promotion and sale, and also its development at the time. Synergic effects in these processes arrive during knowledge application and development, and also intellectual capital value growth in firm-partners of the network organization. In accordance with EU innovation politics regional innovation system enables collaboration of enterprises, research and development institutions, financial support and transfer organizations in network during innovation processes flow. The aim of this system building is greater competitive and higher innovative level of organizations in region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 78-86